2014
DOI: 10.1002/etc.2765
|View full text |Cite
|
Sign up to set email alerts
|

Maternal repeated oral exposure to microcystin‐LR affects neurobehaviors in developing rats

Abstract: Microcystins are toxic peptides secreted by certain water blooms of toxic cyanobacteria. The most widely studied microcystin is microcystin-LR (MC-LR), which exhibits hepatotoxicity and neurotoxicity. However, limited information is available regarding the effects on offspring following maternal exposure. The present study was conducted to observe the effects of progestational exposure to MC-LR on postnatal development in rats. Female Sprague-Dawley rats (28 d old) were randomly divided into a control group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
3
22
0
1
Order By: Relevance
“…Recently, several studies have confirmed the trans-generational toxicity of MCs in zebrafish [143] and rats [142,144]. When adult zebrafish were continuously exposed to MC-LR (1, 5, and 20 g/L) for 30 days, the growth (body weight and body length) of the F1 generation at 60 days post fertilization (dpf) was significantly inhibited even though the embryos and larvae were free of MC exposure [143].…”
Section: Trans-generational Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have confirmed the trans-generational toxicity of MCs in zebrafish [143] and rats [142,144]. When adult zebrafish were continuously exposed to MC-LR (1, 5, and 20 g/L) for 30 days, the growth (body weight and body length) of the F1 generation at 60 days post fertilization (dpf) was significantly inhibited even though the embryos and larvae were free of MC exposure [143].…”
Section: Trans-generational Toxicitymentioning
confidence: 99%
“…Qiao et al [85] reported that MC-LR exposure exerts diverse reproductive toxicity in zebrafish, with females exhibiting more sensitivity than males. However, Li et al [142] demonstrated that male offspring are more susceptible to maternal exposure of MC-LR on memory function than females. Therefore, female reproductive effects of MCs should be strengthened in future studies.…”
Section: Female and Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [158] MCs does not consider this study in calculating the guideline value for MCs in drinking water.…”
Section: Microcystinmentioning
confidence: 94%
“…Indeed, direct injection of MC to rat hippocampus at femtogram levels has been shown to affect learning and memory [153,154,158]. MCs have also been shown to alter fish behavior and learning as well as increase acetylcholinesterase activity in fish brain [152].…”
Section: Effects On Other Tissues From Oral Exposure To Mcsmentioning
confidence: 99%